Análisis del tratamiento mediático en el contexto informativo del Trastorno del Espectro Autista TEA y su incidencia en los procesos de inclusión y formación social en el entorno del Centro Psicoeducativo Integral ISAAC - García Matute, Jessica Mabel (2020)
The present research work aims to carry out a study on the analysis of media treatment in the informative context of Autism Spectrum Disorder, in order to know how they approach? and how often? These issues are given in the media, and their impact on the processes of inclusion and social training in the environment of the Centro Psicoeducativo Integral ISAAC. The media exert a great influence on the inclusion of Autism at the time of making or preparing information, it depends on them whether it is issued with correct language without stigmatizing the condition of children with ASD.............